Cirque du freak : trials of death / 5. - Shan, Darren (Shan, Darren. Saga of Darren Shan, 2001)
Darren begins the Trials of Initiation to prove himself worthy of being a half-vampire, even as the clan's blood foes, the vampaneze, gather near Vampire Mountain.